Effect of Echinacea on gut microbiota of immunosuppressed ducks - Lin, Renzhao; Zhi, Chanping; Su, Yalin; Chen, Jiaxin; Gao, Debao; Li, Sihan; Shi, Dayou (Frontiers in Microbiology, 2023)
Immunosuppression puts animals in a susceptible state and disrupts the balance of intestinal flora, which can increase the risk of disease and cause serious harm to the farm. Echinacea can exert its immunomodulatory effect in various ways, but its influence on intestinal flora is unclear. Therefore, we investigated the effect of Echinacea extract (EE) on gut microbiota in immunosuppressed ducks by 16s-RNA sequencing in this experiment. The results showed that EE significantly improved the weight gain of immunosuppressed ducks (P<0.001). It also increased the immune organ index (P<0.01) and upregulated the levels of TNF-α and IFN-γ (P<0.05) as well as IL-2 in the serum. The lesions of the bursa were evident compared to the spleen and thymus. After treatment in the EE group, the lymphocyte count of the bursa returned to healthy levels and the lesions were significantly improved. The diversity analysis showed that neither of the alpha-diversity indices showed a significant difference (P>0.05). However, the EE group had a trend closer to the healthy group compared to the M group. β-diversity analysis revealed a high degree of sample separation between the healthy and immunosuppressed groups. The sequencing result showed a significantly higher relative abundance of Prevotella and Prevotella_UCG_001 in the dexamethasone-treated group, which could be potential biomarkers of dexamethasone-induced immunosuppression. EE increased the relative abundance of Akkermansia, Bacteroides, and Alistipes and significantly decreased the relative abundance of Megamonas, Streptococcus, and Enterococcus (P<0.05). The results showed that Echinacea extract improves the development of immunosuppressed ducks and modulates intestinal immune function by increasing the abundance of beneficial bacterial genera in the intestine.